1971
DOI: 10.2320/matertrans1960.12.71
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Characteristics of Magnesium-4wt% Zinc Alloy

Abstract: of electrical resistivity and hardness measurements, the X-ray Debye-Scherrer method and electron-microscopic observations. From the kinematic point of view the aging sequences were analyzed using the C-curve obtained by plotting the logarithm of the incubation time as a function of the reciprocal of the absolute aging temperature.The results showed that the tion of G. P. zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Addition of Cu also increases the eutectic temperature and permits the use of higher solution treatment temperatures. [2,3] The precipitation sequence in the Cu-containing Mg-Zn alloys above 150°C [4] has been reported to be the same as the most probable aging sequence for a binary Mg-Zn alloy: [5][6][7][8][9][10][11][12] SSSS ! solute clusters !…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Addition of Cu also increases the eutectic temperature and permits the use of higher solution treatment temperatures. [2,3] The precipitation sequence in the Cu-containing Mg-Zn alloys above 150°C [4] has been reported to be the same as the most probable aging sequence for a binary Mg-Zn alloy: [5][6][7][8][9][10][11][12] SSSS ! solute clusters !…”
Section: Introductionmentioning
confidence: 98%
“…[14] The precipitation of GP zones was also confirmed by the effect that low-temperature preaging had on hardness and microstructure evolution during subsequent artificial aging. [7,8,15] A more recent study showed that the precipitation in Mg-Zn alloy commences by clustering of Zn atoms, while during aging at intermediate temperatures (up to about 100°C), four to six different types of precipitates were simultaneously present in the microstructure leading to hardening of a significant magnitude. [16] Age hardening at ambient temperature after quenching from the solution heat treatment temperature is common to age-hardenable aluminum alloys; however, this was not observed in age-hardenable magnesium alloys in the past.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54][55][56] The aging curves of two binary Mg-Zn alloys are provided in Figure 5(a). Depending on the alloy composition and aging temperatures, it is commonly accepted in the literature [6,8,30] that the decomposition of the supersaturated solid-solution matrix phase reportedly involves the formation of G.P.…”
Section: Phase Equilibria and Precipitationmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] For example, Mg-5 mass%Zn alloy exhibits age hardening by the precipitation of needle shaped MgZn phase after prolonged aging at $422 K. 10) To date, however, TMT to attain microstructural stability has not been investigated in magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%